1993
DOI: 10.1093/bja/71.4.544
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the Relaxant Action of Ketamine on Isolated Porcine Trachealis Muscle

Abstract: Ketamine is a potent bronchodilator, but its mode of action is unclear. We have studied the effect of ketamine on the peripheral vagus nerve motor pathway of isolated porcine trachealis muscle. Postsynaptic nicotinic cholinergic receptors of the intramural ganglia were stimulated selectively with 1,1-dimethyl-4-phenyl-piperazinium iodide, post-ganglionic nerve fibres with electrical field stimulation (in the presence of hexamethonium) and muscarinic cholinergic receptors with acetylcholine (in the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 0 publications
0
13
0
2
Order By: Relevance
“…No significant depression of respiration by ketamine [22,23], diazepam [23], droperidol [24] and eptazocine [25] in the respective clinical doses has been demonstrated. In addition, ketamine [26][27][28][29], opioids [5,30], diazepam [31], droperidol [24], and vecuronium [32] have been shown not to stimulate bronchial smooth muscle in the clinical doses used in this study, and this accounts for the lack of significant effects on respiration of our TIVA regime. In fact, a 72-yearold woman with a recent history of several complicated asthmatic attacks underwent uneventful subtotal gastrectomy under TIVA plus epidural eptazocine.…”
Section: Discussionmentioning
confidence: 77%
“…No significant depression of respiration by ketamine [22,23], diazepam [23], droperidol [24] and eptazocine [25] in the respective clinical doses has been demonstrated. In addition, ketamine [26][27][28][29], opioids [5,30], diazepam [31], droperidol [24], and vecuronium [32] have been shown not to stimulate bronchial smooth muscle in the clinical doses used in this study, and this accounts for the lack of significant effects on respiration of our TIVA regime. In fact, a 72-yearold woman with a recent history of several complicated asthmatic attacks underwent uneventful subtotal gastrectomy under TIVA plus epidural eptazocine.…”
Section: Discussionmentioning
confidence: 77%
“…[17] Ketamine by effect on the pre-ganglionic fibers, nicotinic receptors in the post-synaptic membrane of intramural ganglion, the muscarinic receptors, and the post-synaptic fibers can decrease the contractile response of the smooth muscles. [18] As Durieux showed, ketamine can inhibit muscarinic receptor signaling significantly. [19] Furthermore, ketamine by effect on the receptors of NMDA in the cortex of the brain can have analgesic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Contreras et al [13] reported that ketamine blocked the toxic effects of neostigmine and physostigmine. Wilson et al [14] studied the effect of ketamine on the peripheral vagus nerve motor pathway of the isolated porcine trachealis muscle. They concluded that ketamine interacted with the peripheral vagus nerve by decreasing the excitability of the nicotinic ACh receptors of the parasympathetic postganglionic neurons.…”
Section: Discussionmentioning
confidence: 99%